HUBUNGAN KUALITAS TIDUR DENGAN TINGKAT KECEMASAN DAN STRES PADA MAHASISWA TINGKAT AKHIR DI UNIVERSITAS YATSI MADANI - Siti Romizatul Halawiyah; AYG Wibisono; Ida Faridah (Nusantara Hasana Journal, 2022)
Sleep quality refers to a person’s pleasure with his sleep and receiving an appropriate amount of sleep for his needs, being one of the triggers for the level of worry, illness, fatigue, environment, lifestyle, alcohol or drugs, nutrition that can cause anxiety and stress and become the main trigger among students who are working on thesis. This study aims to determine the relationship between sleep quality and anxiety and stress levels in nursing students at Yatsi Madani UniversityThis type of research is a quantitative method with a comparative causal design and cross-sectional methodology. The sample in this study used random sampling with the slovin formula, it was found that 152 respondents from the final level of 8th semester students of Yatsi Madani University had met the inclusion criteria set. The results of the Chi Square test of anxiety levels with sleep quality obtained a P-value of 0.001 <0.05 indicating that there is a relationship between anxiety levels and sleep quality in students, and the results of the Chi Square Test of Stress Levels with Sleep Quality obtained P-values. value 0.000 <0.05 indicates that there is a relationship between stress levels and sleep quality in students. There is a significant relationship between sleep quality and the level of anxiety and severe stress experienced by final year students at Yatsi Madani University who are working on a thesis.